Nutritional composition of low protein and phenylalanine-restricted dishes prepared for phenylketonuric patients - Pimentel, Filipa B. (2015)
Nutritional management is essential for Phenylketonuria (PKU) treatment, consisting in a semi-synthetic and low phenylalanine (Phe) diet, which includes strictly controlled amounts of low protein natural foods (essentially fruits and vegetables) supplemented with Phe-free protein substitutes and dietetic low-protein products. PKU diet has to be carefully planned, providing the best ingredient combinations, so that patients can achieve good metabolic control and an adequate nutritional status. Hereupon, it is mandatory to know the detailed composition of natural and/or cooked foodstuffs prepared specifically for these patients. We intended to evaluate sixteen dishes specifically prepared for PKU patients, regarding the nutritional composition, Phe and tyrosine (Tyr) contents, fatty acids profile, and vitamins E and B12 amounts. The nutritional composition of the cooked samples was 15.5–92.0 g/100 g, for moisture; 0.7–3.2 g/100 g, for protein; 0.1–25.0 g/100 g, for total fat; and 5.0–62.0 g/100 g, for total carbohydrates. Fatty acids profile and vitamin E amount reflected the type of fat used. All samples were poor in vitamin B12 (0.3–0.8 μg/100 g). Boiled rice presented the highest Phe content: 50.3 mg/g of protein. These data allow a more accurate calculation of the diet portions to be ingested by the patients according to their individual tolerance.